Individual Variation in Fathers’ Testosterone Reactivity to Infant Distress Predicts Parenting Behaviors with their 1-Year-Old Infants - Kuo, Patty X. (Dev Psychobiol, 2015)
Positive father involvement is associated with positive child outcomes. There is great variation in fathers’ involvement and fathering behaviors, and men’s testosterone (T) has been proposed as a potential biological contributor to paternal involvement. Previous studies investigating testosterone changes in response to father-infant interactions or exposure to infant cues are unclear as to whether individual variation in T is predictive of fathering behavior. We show that individual variation in fathers’ T reactivity to their infants during a challenging laboratory paradigm (Strange Situation) uniquely predicted fathers’ positive parenting behaviors during a subsequent father-infant interaction, in addition to other psychosocial determinants of paternal involvement, such as dispositional empathy and marital quality. The findings have implications for understanding fathering behaviors and how fathers can contribute to their children’s socioemotional development.